2018
DOI: 10.1073/pnas.1803406115
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific disruption of STING-dependent antiviral cellular defenses by the Zika virus NS2B3 protease

Abstract: The limited host tropism of numerous viruses causing disease in humans remains incompletely understood. One example is Zika virus (ZIKV), an RNA virus that has reemerged in recent years. Here, we demonstrate that ZIKV efficiently infects fibroblasts from humans, great apes, New and Old World monkeys, but not rodents. ZIKV infection in human-but not murine-cells impairs responses to agonists of the cGMP-AMP synthase/stimulator of IFN genes (cGAS/STING) signaling pathway, suggesting that viral mechanisms to evad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 60 publications
5
171
1
1
Order By: Relevance
“…Thus, Stat2 −/− mice succumb to ZIKV infection, but transgenic mice expressing human STAT2 only exhibit disease in the context of ZIKV strains with additional mouse-adaptive mutations (4, 44). In addition, the ZIKV NS2B-NS3 protease targets human but not murine STING, resulting in sustained IFN production and diminished viral replication in mouse cells (3). However, mice lacking STING were not more susceptible to ZIKV than wild-type mice (2, 3), implying that STING is a contributing but not dominant factor restricting ZIKV infection in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Stat2 −/− mice succumb to ZIKV infection, but transgenic mice expressing human STAT2 only exhibit disease in the context of ZIKV strains with additional mouse-adaptive mutations (4, 44). In addition, the ZIKV NS2B-NS3 protease targets human but not murine STING, resulting in sustained IFN production and diminished viral replication in mouse cells (3). However, mice lacking STING were not more susceptible to ZIKV than wild-type mice (2, 3), implying that STING is a contributing but not dominant factor restricting ZIKV infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mice would be an attractive system for such studies due their low cost and genetic tractability and mice have proven to be a valuable system for studying other flaviviruses, such as West Nile virus (WNV). However, studies of ZIKV in mice are confounded because mouse type I interferon (IFN-αβ) signaling restricts ZIKV replication (2), in part due to the inability of ZIKV to antagonize murine STAT2 and STING (3-6). This results in diminished ZIKV replication in immune competent mice and has led most groups to use IFN-deficient mouse models including mice lacking the type I and/or type II IFN receptors (e.g., Ifnar1 −/− or Ifnar1 −/− Ifngr1 −/− double knockout), mice with defects in IFN induction or signaling (e.g., Irf3 −/− Irf5 −/− Irf7 −/− or Stat2 −/− ), or mice treated with IFNAR1-blocking antibody (7).…”
Section: Introductionmentioning
confidence: 99%
“…Beside regulating eIF2α phosphorylation and hijacking key SG proteins, RNA viruses were reportedly capable of interfering SGs assembly through cleaving and redistributing SGs nucleating factors [74]. It was previously reported that ZIKV NS2B-NS3 protease could cleave host antiviral factors to impair intrinsic host defense; intriguingly, ZIKV did not mediate the cleavage of SG factors even though SGs assembly was affected by ZIKV NS3 and NS2B-NS3 protease [77][78][79][80][81]. Nonetheless, ZIKV infection was found to facilitate the redistribution of TIAR to viral replication sites, which correlates to viral replication output [77,78,81].…”
Section: Zikv Inhibits Cytoplasmic Stress Granules Formationmentioning
confidence: 99%
“…Several viruses employ strategies to degrade STING to prevent its activation by 2 0 3 0 -cGAMP (Figure 4). Similar to degradation of cGAS, DENV and other related flaviviruses proteolytically cleave STING using the viral protease complex NS2B3, blocking induction of signaling [45,46 ]. In addition, the HCMV IE86 protein promotes STING degradation in the proteasome, restricting activation of downstream signaling [47].…”
Section: Pathogens Block Sting Signalosome Assemblymentioning
confidence: 99%